Role of School Bullying Involvement in Depression, Anxiety, Suicidality, and Low Self-Esteem Among Adolescents With High-Functioning Autism Spectrum Disorder - Chou, Wen-Jiun; Wang, Peng-Wei; Hsiao, Ray C.; Hu, Huei-Fan; Yen, Cheng-Fang (Frontiers in Psychiatry, 2020)
The aim of this study was to examine the differences in the levels of depression, anxiety, suicidality, and self-esteem among adolescents with high-functioning autism spectrum disorder (ASD) who had various experiences of school bullying involvement in Taiwan. A total of 219 adolescents with high-functioning ASD participated in this study. According to their experiences of school bullying involvement in the previous 1 year, as measured using the Chinese version of the School Bullying Experience Questionnaire, the participants were divided into the following groups: pure perpetrators, pure victims, perpetrator-victims, and neutrals. The levels of depression on the Center for Epidemiological Studies Depression Scale, anxiety on the Multidimensional Anxiety Scale for Children, suicidality on the 5-item questionnaire from the epidemiological version of the Kiddie Schedule for Affective Disorders and Schizophrenia, and self-esteem on the Rosenberg Self-Esteem Scale were compared among the aforementioned groups. The results indicated that compared with the self-reported neutrals, the self-reported perpetrator-victims and pure victims had more severe depression and anxiety. No difference in depression, suicidality, anxiety and self-esteem was found among the four groups of various parent-reported bullying involvement experiences. Mental health problems in adolescents with ASD who were the self-reported pure bullying victims or perpetrator-victims should be routinely surveyed.